2020
DOI: 10.1101/2020.02.07.939389
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Pathogenicity of SARS-CoV-2 in hACE2 Transgenic Mice

Abstract: AbstractSevere acute respiratory syndrome CoV-2 (SARS-CoV-2) caused the Corona Virus Disease 2019 (COVID-19) cases in China has become a public health emergency of international concern (PHEIC). Based on angiotensin converting enzyme 2 (ACE2) as cell entry receptor of SARS-CoV, we used the hACE2 transgenic mice infected with SARS-CoV-2 to study the pathogenicity of the virus. Weight loss and virus replication in lung were observed in hACE2 mice infected with SARS-CoV-2. The typ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
598
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

6
3

Authors

Journals

citations
Cited by 441 publications
(632 citation statements)
references
References 10 publications
29
598
1
4
Order By: Relevance
“…However, while plasma from mice infected with SARS-CoV virus could react with its autologous S ectodomain (p-value < 8e-6, two-tailed t-test, Figure 2C) and RBD (p-value < 2e-5, two-tailed t-test, Figure 2D), the reactivity of plasma from mice infected with SARS-CoV-2 virus to its autologous S ectodomain and RBD could not be observed in this assay (p-value > 0.28, two-tailed t-test, Figure 2A-B). Unlike SARS-CoV virus, which can replicate in wild-type mice (Yang et al, 2004), it has been recently shown that SARS-CoV-2 is only able to replicate in human ACE2-expression transgenic mice but not wild-type mice (Bao et al, 2020), which then can explain the weak immune response from SARS-CoV-2-infected wild-type mice in this study.…”
Section: Resultsmentioning
confidence: 69%
“…However, while plasma from mice infected with SARS-CoV virus could react with its autologous S ectodomain (p-value < 8e-6, two-tailed t-test, Figure 2C) and RBD (p-value < 2e-5, two-tailed t-test, Figure 2D), the reactivity of plasma from mice infected with SARS-CoV-2 virus to its autologous S ectodomain and RBD could not be observed in this assay (p-value > 0.28, two-tailed t-test, Figure 2A-B). Unlike SARS-CoV virus, which can replicate in wild-type mice (Yang et al, 2004), it has been recently shown that SARS-CoV-2 is only able to replicate in human ACE2-expression transgenic mice but not wild-type mice (Bao et al, 2020), which then can explain the weak immune response from SARS-CoV-2-infected wild-type mice in this study.…”
Section: Resultsmentioning
confidence: 69%
“…The nasal/throat/anal swab samples and mainly tissue compartments collected from infected monkeys were tested for SARS-CoV-2 RNA by quantitative real-time reverse transcription-PCR (qRT-PCR). Total RNA was extracted and reverse transcription was performed as previously described 7 . qRT-PCR reactions were carried out on an ABI 9700 Real-time PCR system (Applied Biosystems Instrument), the cycling protocol and the primers as follows: 50°C for 2 min, 95°C for 2 min, followed by 40 cycles at 95°C for 15 s and 60°C for 30 s, and then 95°C for 15 s, 60°C for 1 min, 95°C for 45 s. Forward primer: 5’-TCGTTTCGGAAGAGACAGGT-3’, Reverse primer: 5’-GCGCAGTAAGGATGGCTAGT-3’.…”
Section: Methodsmentioning
confidence: 99%
“…For immunohistochemistry (IHC) staining to identify the antigen of SARS-CoV-2, paraffin dehydrated sections (3-4 µm in thickness) were treated with an antigen retrieval kit (Boster, AR0022) for 1 min at 37°C and quenched for endogenous peroxidases in 3% H 2 O 2 in methanol for 10 min. After blocking in 1% normal goat serum for 1 hour at roomtemperature, the slices were stained with 7D2 monoclonal antibody (laboratory preparation 7 ) at 4°C overnight, following with the incubation of HRP-labeled goat anti-mouse IgG (Beijing ZSGB Biotechnology, ZDR-5307) for 1 hour. Then, the slices were visualized by incubation with 3,30-diaminobenzidine tetrahydrochloride (DAB) and the image was viewed under an Olympus microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Since December of 2019, scientists all over the world have been working to establish animal model of COVID-19. So far there are several models reported in preprinted journals or peer-reviewed published journals, including two small murine models (hACE2 transgenic mouse 14 and Gold Syrian hamster 15 ), one ferret model 16 Retrospective studies of clinical features of COVID-19 show that older patients have more severe diseases, which may be associated with comorbidities, including tumor, diabetes, obesity, hypertension, heart diseases and so on [18][19][20] . These underlying diseases may make senior patients more susceptible to SARS-CoV-2 infection and worsen COVID-19.…”
Section: Sars-cov-2 Recently Reported As Another Novel Coronavirus Ementioning
confidence: 99%